2003
DOI: 10.1002/atr.5670370302
|View full text |Cite
|
Sign up to set email alerts
|

The car pooling problem: Heuristic algorithms based on savings functions

Abstract: The present research deals with car pooling as a means of making better use of existing infrastructure and as a means of reducing traffic congestion with all its associated induced effects. Car pooling schemes involve several drivers getting together to share a private vehicle simultaneously, in order to reach their destinations points according to a semi-common route rather than each driver using their own vehicle. The Car Pooling Problem belongs to the non-polynomial computational complexity family of operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…There have been a few studies regarding the carpool optimization problem. Ferrari et al [1] designed several different automatic and heuristic data processing routines based on savings functions to support efficient matching in carpool schemes. The problem involved locating users at their origin locations who needed to reach the same destination point given temporal and topographical constraints.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few studies regarding the carpool optimization problem. Ferrari et al [1] designed several different automatic and heuristic data processing routines based on savings functions to support efficient matching in carpool schemes. The problem involved locating users at their origin locations who needed to reach the same destination point given temporal and topographical constraints.…”
Section: Introductionmentioning
confidence: 99%
“…One attempt to solve the LTCPP is based on saving functions [13]. Automatic and heuristic data processing routines were developed by the authors to allow efficient matching of rides for passengers and riders.…”
Section: Introductionmentioning
confidence: 99%
“…In (Guo et al, 2012) a "Genetic Adaptive algorithm" was used, while in (Calvo et al, 2004) a system is presented using web GIS and SMS where the problem of carpooling is solved with a heuristic algorithm. Also in (Ferrari et al, 2003) a "Heuristic algorithms based on savings functions" was proposed. Finally (Santi et al, 2014) has been showed and quantified "the benefits of vehicle pooling with shareability networks".…”
Section: Introductionmentioning
confidence: 99%